2016
DOI: 10.1088/2040-8978/18/6/063001
|View full text |Cite
|
Sign up to set email alerts
|

Roadmap on optical rogue waves and extreme events

Abstract: The pioneering paper 'Optical rogue waves' by Solli et al (2007 Nature 450 1054) started the new subfield in optics. This work launched a great deal of activity on this novel subject. As a result, the initial concept has expanded and has been enriched by new ideas. Various approaches have been suggested since then. A fresh look at the older results and new discoveries has been undertaken, stimulated by the concept of 'optical rogue waves'. Presently, there may not by a unique view on how this new scientific te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
140
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 256 publications
(143 citation statements)
references
References 198 publications
(314 reference statements)
3
140
0
Order By: Relevance
“…Laser systems displaying extreme optical pulses, often referred to as optical rogue waves (RWs) [1], are being intensively investigated as they are excellent test beds to study extreme fluctuations under controlled conditions [2][3][4][5][6][7][8][9]. Rogue waves have been observed in many systems and were initially found in hydrodynamics, where occasionally, huge waves in ocean waters have been reported that, in contrast to tsunamis or solitons, can appear from nowhere, disappear in a short spatial length and do not necessarily propagate for long distances [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Laser systems displaying extreme optical pulses, often referred to as optical rogue waves (RWs) [1], are being intensively investigated as they are excellent test beds to study extreme fluctuations under controlled conditions [2][3][4][5][6][7][8][9]. Rogue waves have been observed in many systems and were initially found in hydrodynamics, where occasionally, huge waves in ocean waters have been reported that, in contrast to tsunamis or solitons, can appear from nowhere, disappear in a short spatial length and do not necessarily propagate for long distances [10].…”
Section: Introductionmentioning
confidence: 99%
“…Optical rogue waves have also been investigated in laser models that include spatial degrees of freedom (one or two dimensions) [9]. While in these models extreme pulses might still be generated by a similar mechanism as in the rate-equation model (the presence of a narrow-channel or a "RW door" in the phase space), due to the high-dimensionality of the phase space this special region is difficult to identify.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rogue wave research flourishes now in both theoretical and experimental aspects [10,12,14], providing novel perspectives for the manifestation of extreme waves in a variety of nonlinear media. To reflect the diversity and complexity of media, it requires the study of the propagation models that go beyond the scalar nonlinear Schrödinger (NLS) equation, such as the extended scalar models [15][16][17][18] and the coupled multicomponent models [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The propagation of partially coherent nonlinear optical waves is a subject of growing interest in different fields of investigations, such as, e.g., supercontinuum (SC) generation [1,2], rogue waves [3][4][5][6], shock waves [7][8][9], nonlinear interferometry [10,11], or incoherent wave propagation in homogeneous [12][13][14][15][16], discrete [17], multimode [18,19] and single-mode fibers nearby the integrable limit [20][21][22]. From a different perspective, optical cavities and lasers offer an interesting experimental platform to study different regimes of optical turbulence [12,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%